2016
DOI: 10.1016/j.watres.2016.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between mixed liquors of two side-stream membrane bioreactors treating wastewaters from waste management plants with high and low solids anaerobic digestion

Abstract: In the last years, biological treatment plants for the previously separated organic fraction from municipal solid wastes (OFMSW) have gained importance. In these processes a liquid effluent (liquid fraction from the digestate and leachate from composting piles), which has to be treated previously to its discharge, is produced. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Two full-scale MBRs (WWTP-A and WWTP-B) that treat lixiviates from plants recycling the previously separated organic fraction from the municipal solid wastes [ 45 , 46 ] were sampled. In the WWTP-A, the Anaerobic Digestion (AD) is carried out by means of a high solids system (dry process, i.e., solids concentration higher than 15%) and in the WWTP-B, the AD is carried out by means of a low solids system (wet-process, i.e., solids concentration that is lower than 10%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two full-scale MBRs (WWTP-A and WWTP-B) that treat lixiviates from plants recycling the previously separated organic fraction from the municipal solid wastes [ 45 , 46 ] were sampled. In the WWTP-A, the Anaerobic Digestion (AD) is carried out by means of a high solids system (dry process, i.e., solids concentration higher than 15%) and in the WWTP-B, the AD is carried out by means of a low solids system (wet-process, i.e., solids concentration that is lower than 10%).…”
Section: Methodsmentioning
confidence: 99%
“…In the WWTP-A, the Anaerobic Digestion (AD) is carried out by means of a high solids system (dry process, i.e., solids concentration higher than 15%) and in the WWTP-B, the AD is carried out by means of a low solids system (wet-process, i.e., solids concentration that is lower than 10%). Both WWTPs were designed to eliminate organic matter and nitrogen [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MBRs are wastewater treatment processes that integrate a permselective membrane with a biological process (Judd 2010). The membrane serves as an advanced treatment unit for complete TSS removal and as a barrier to microorganisms , Zuriaga-Agustí et al 2016. However, MBRs are still facing a major operating problem: membrane fouling (Hashemi et al 2016a, b;Zuriaga-Agustí et al 2016).…”
Section: Membrane Bioreactorsmentioning
confidence: 99%
“…The membrane serves as an advanced treatment unit for complete TSS removal and as a barrier to microorganisms , Zuriaga-Agustí et al 2016. However, MBRs are still facing a major operating problem: membrane fouling (Hashemi et al 2016a, b;Zuriaga-Agustí et al 2016). Hashemi et Khodabakhshi reported that the use of granular activated carbon within a MBR reduces membrane fouling while also removing a significant level of recalcitrant and the biorefractory compound found in composting leachates (Hashemi and Khodabakhshi 2016).…”
Section: Membrane Bioreactorsmentioning
confidence: 99%